1976
DOI: 10.1136/bmj.2.6041.907
|View full text |Cite
|
Sign up to set email alerts
|

Titanium-strip cranioplasty.

Abstract: SummaryTitanium strips have been used to repair skull defects when preformed metal plates are not available and simple wiring would not be enough. The technique is simple, obviates the need to dissect the dura mater, and gives greater resistance to further impact injury than an inlay technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1980
1980
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…9 From a variety of different repair materials, titanium mesh has become a popular material for cranioplasty due to its good compatibility with human tissue, light weight, thinness, hardness, and ability to be easily shaped. 1,10,13 In recent years, digital computer techniques have been widely used for molding titanium mesh for cranioplasty. 2,11,12 In this technique, head CT scan data, obtained from the contralateral side of the skull defect, is…”
mentioning
confidence: 99%
“…9 From a variety of different repair materials, titanium mesh has become a popular material for cranioplasty due to its good compatibility with human tissue, light weight, thinness, hardness, and ability to be easily shaped. 1,10,13 In recent years, digital computer techniques have been widely used for molding titanium mesh for cranioplasty. 2,11,12 In this technique, head CT scan data, obtained from the contralateral side of the skull defect, is…”
mentioning
confidence: 99%
“…For example, recombinant human bone morphogenetic proteins (rhBMPs) were found to induce osteogenesis 32 and have since been successfully translated into clinical use. 74 Combinatorial approaches incorporating BMPs like BMP-2 or BMP-7 have since been developed [75][76][77][78] and we have also shown that discontinuous triphasic release of BMP from polycaprolactone (PCL) scaffolds led to a higher bone volume fraction and trabecular thickness. 79 To provide an alternative to or complement BMPs, You et al intensively studied heparan sulfates (HS), which are glycosaminoglycan sugars.…”
Section: Surface Modification Strategiesmentioning
confidence: 96%
“…Titanium strips have been used to repair skull defects in situations where pre-formed metal plates are not obtainable and wiring is not adequate [72]. This particular method is simple, does not require dissection of the dura mater, and offers better resistance to additional impact injury than an inlay technique [72]. The strips of titanium IMI 115, 0-6mm thick, are cut to numerous widths and lengths as shown in Table 4.…”
Section: Titanium-strips Cranioplastymentioning
confidence: 99%